Functionalized nanofiller for polymers – preparation, properties and application - Wierzbicka, E.; Legocka, I.; Wardzińska-Jarmulska, E.; Szczepaniak, B.; Krzyżewski, M. (Polimery, 2021)
The study on the modification of polymers using afunctionalized nanofiller has been described. The structure and properties of the native halloysite as well as the methods of preparation and the properties of halloysite modified by urea were characterized. The mechanical properties of the composites based on epoxy resin, urea-formaldehyde resin and phenol-formaldehyde resin containing from 1 to 4 wt % urea-modified halloysite, added in situ during the resin synthesis, were investigated. The effect of urea-modified halloysite on reducing the formaldehyde emission from phenol- and urea-formaldehyde resins has been demonstrated.